2018
DOI: 10.1186/s12879-018-3180-z
|View full text |Cite
|
Sign up to set email alerts
|

Sputum signatures for invasive pulmonary aspergillosis in patients with underlying respiratory diseases (SPARED): study protocol for a prospective diagnostic trial

Abstract: BackgroundInvasive pulmonary aspergillosis (IPA) has been increasingly reported in patients with underlying respiratory diseases (URD). Early diagnosis of IPA is crucial for mortality reduction and improved prognosis, yet remains difficult. Existing diagnostic tools for IPA largely rely on the detection of biomarkers based on serum or bronchoalveolar lavage fluid (BALF), both of which have their limitations. The use of sputum sample is non-invasive, and Aspergillus detection is feasible; however, the usefulnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…CRP and PCT are diagnostic indicators of clinical infectious diseases. PCT can reflect the activity of systemic inflammatory reaction, while CRP is an acute inflammatory phase protein that is commonly used in the detection of inflammatory reaction [ 18 ]. It is reported that many patients with PI have increased secretion of pulmonary inflammatory factors, which will lead to substantial inflammation of alveolar cavity, interstitial lung, and airway.…”
Section: Discussionmentioning
confidence: 99%
“…CRP and PCT are diagnostic indicators of clinical infectious diseases. PCT can reflect the activity of systemic inflammatory reaction, while CRP is an acute inflammatory phase protein that is commonly used in the detection of inflammatory reaction [ 18 ]. It is reported that many patients with PI have increased secretion of pulmonary inflammatory factors, which will lead to substantial inflammation of alveolar cavity, interstitial lung, and airway.…”
Section: Discussionmentioning
confidence: 99%
“…The search for a circulating molecule that can serve as a disease biomarker is hampered by the following unresolved issues: (i) the low concentration of circulating fungal molecules, which requires detection by use of either a monoclonal antibody with high-affinity and -avidity characteristics (e.g., galactomannan [GM]) or by a process of signal amplification (␤1,3 glucans and DNA), and (ii) an incomplete understanding of the kinetics of release of the various circulating fungal molecules. Biomarkers can be searched in serum urine, BAL fluid, and even sputum (104)(105)(106).…”
Section: Figmentioning
confidence: 99%
“…Induced sputum samples were collected and processed as previously described [ 22 ] for GM, LFD, PCR, TAFC, and bmGT assays. Specimens with a squamous cell percentage >50% or cell viability <40% were deemed unqualified and excluded.…”
Section: Methodsmentioning
confidence: 99%
“…[ 22 ] The method has a limit of detection of ≤1 ng/mL and a lower limit of quantitation of 1.56 ng/mL for both TAFC and bmGT. [ 22 ]…”
Section: Methodsmentioning
confidence: 99%